2020
DOI: 10.21203/rs.2.20889/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Study of the Effect of Macrolide Antibiotics Erythromycin, Clarithromycin, and Azithromycin on the ERG1 Gene Expression in H9c2 Cardiomyoblast Cells

Abstract: Background: Macrolides are a clinically well-established class of antibiotics. Macrolides induce cardiotoxicity by blocking ERG potassium channels in cardiac myocytes. The aim of this study was to compare the effects of erythromycin, clarithromycin and azithromycin on cell viability and expression of ERG1 gene in H9c2 cells. Methods: Cell viability and ERG1 gene expression of H9c2 cells in 3 different concentrations, 1, 10 and 25µg/ml, after 48 and 72 hours were determined by MTT test and Real time-PCR method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In addition to TIM-3, the activation of the PD-1/PD-L1 pathway in severe H1N1 influenza A infection has been demonstrated in tissue samples of the lower respiratory tract in pediatric patients and their dendritic and T cells as well [21,22]. PD-L1 expression levels are inversely related to the number of CD8 + T cells in these patients, and inhibition of this pathway improves the number and function of CD8 + T cells [23]. Rutigliano et al showed that decreased CD8 + T cells activity in influenza A virus infection in mice was associated with increased PD-1 expression [24].…”
Section: The Common Pattern Of Virus-induced Hyperinflammation Of Respiratory Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to TIM-3, the activation of the PD-1/PD-L1 pathway in severe H1N1 influenza A infection has been demonstrated in tissue samples of the lower respiratory tract in pediatric patients and their dendritic and T cells as well [21,22]. PD-L1 expression levels are inversely related to the number of CD8 + T cells in these patients, and inhibition of this pathway improves the number and function of CD8 + T cells [23]. Rutigliano et al showed that decreased CD8 + T cells activity in influenza A virus infection in mice was associated with increased PD-1 expression [24].…”
Section: The Common Pattern Of Virus-induced Hyperinflammation Of Respiratory Virusesmentioning
confidence: 99%
“…The antiviral activity is attributed to their binding to IFN-receptor and inducing STAT1/2, IRF7, IRF9, and production of ISGF3 as well [22]. Clarithromycin and Leucomycin are the examples of Macrolides, used against the influenza virus to increase IFN-α production [23,38]. Azithromycin is another macrolide that inhibits rhinoviruses via potentiating IFN-I signaling.…”
Section: Interventions Of Ifns and Their Agonists With Sars-cov-2 Infectionmentioning
confidence: 99%